Effect of Exogenous Glutathione and Selenium on Cadmium-Induced Changes in Cadmium and Mineral Concentrations and Antioxidative Metabolism in Maize Seedlings - Sun, Hong-Yan; Wang, Xiao-Yun; Dai, Hua-Xin; Zhang, Guo-Ping; Wu, Fei-Bo (Asian Journal of Chemistry, 2013)
A hydroponic experiment was carried out to study the modulation of exogenous reduced glutathione and selenium in antioxidant defense system and microelement uptake against cadmium-toxicity in maize seedlings. The results showed that 50 μM cadmium increased accumulation of H2O2 and malondialdehyde but reduced plant height, root length, chlorophyll content (SPAD value) and biomass. Antioxidant enzyme activities of root/leaf peroxidase and leaf superoxide dismutase increased significantly under cadmium stress, while leaf catalase decreased significantly. Moreover, cadmium-stress reduced manganese concentrations both in shoots and roots. Significantly negative correlation was discovered between manganese and cadmium concentration in different plant organs. Addition of 2.5 μM selenium or pretreated with 100 μM glutathione for 24 h significantly alleviated cadmium-induced growth inhibition and dramatically diminished leaf H2O2 and root malondialdehyde accumulation. Se addition or glutathione pretreatment significantly decreased cadmium concentration in roots/shoots, increased root iron level, while glutathione reduced zinc uptake. Furthermore, GSH/Se counteracted cadmium-induced alterations of certain antioxidant enzymes, e.g. brought root/leaf peroxidase and leaf superoxide dismutase activities down towards to the control level, but elevated root ascorbate peroxidase activity. These data suggest that reduced cadmium concentration and diminished cadmium-induced H2O2 and malondialdehyde accumulation in plants could be principal protective mechanism for the exogenous glutathione/selenium against cadmium toxicity.